Piezophotocatalytic Activity of PVDF/Fe3O4 Nanofibers: Effect of Ultrasound Frequency and Light Source on the Decomposition of Methylene Blue - Rabadanova, Alina; Selimov, Daud; Gulakhmedov, Rashid R; Magomedova, Asiyat G; Ronoh, Kipkurui; Částková, Klára; Sobola, Dinara; Kaspar, Pavel; Shuaibov, Abdulatip; Abdurakhmanov, Magomed G; Rabadanov, Murtazali K; Ramazanov, Shikhgasan M; et al. (ACS omega, 2025)
This study investigates the piezophotocatalytic (PPhC) performance of electrospun nanofibrous membranes composed of polyvinylidene fluoride (PVDF) and magnetite (Fe3O4) nanoparticles. The composite membranes were synthesized via electrospinning, with optimized parameters to promote β-phase crystallinity and uniform fiber morphology. Structural and phase analyses by SEM, FTIR, Raman, and XPS confirmed the predominance of the electroactive β-phase (99.8%) in the composite, as well as strong interfacial interaction between Fe3O4 and the PVDF matrix. The composites exhibited significantly enhanced surface hydrophilicity and piezoelectric response compared to pristine PVDF. The piezoelectric potential generation was confirmed using a flexible piezoelectric nanogenerator (PENG), where a 3 × 1 cm membrane generated output voltages up to ∼2 V under periodic mechanical deformation at 4 Hz. Photocatalytic and piezophotocatalytic degradation of methylene blue (MB) was carried out under UV and visible light at varying ultrasonic frequencies. Maximum PPhC efficiency was achieved at 40 kHz, with 93% dye degradation in 60 min and a reaction rate constant exceeding the sum of photocatalysis and piezocatalysis by 13%, indicating a pronounced synergistic effect. Reactive oxygen species trapping and fluorescence spectroscopy confirmed •OH as the dominant oxidant. H2O2 productivity under PPhC reached 1700 μmol·g-1·h-1 in pure water, with a light-to-chemical energy conversion efficiency of 0.26%. Additionally, experiments conducted under an alternating magnetic field (0.3 T, 1.3 Hz) demonstrated 50% MB degradation within 240 min, revealing the contribution of magnetoelectric coupling as an alternative catalytic activation mechanism. The results suggest that PVDF/Fe3O4 nanocomposites are highly promising for multifunctional catalytic applications, combining piezoelectric, photo-, and magnetoelectric activation for efficient water purification and green oxidant production.